2022
DOI: 10.1007/s40974-022-00261-6
|View full text |Cite
|
Sign up to set email alerts
|

ASEAN’s energy transition: how to attract more investment in renewable energy

Abstract: The energy transition is progressing slowly in the ten member states of the Association of Southeast Asian Nations (ASEAN). To achieve ASEAN’s target of 23% renewables in the primary energy supply by 2025, the region would need to invest USD 27 billion in renewable energy every year. However, the ASEAN countries attracted no more than USD 8 billion annually from 2016 to 2021. Through a comparative review of three key factors for attracting investment—renewable energy legislation, energy governance reform, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…Energy transition is resource intensive. Southeast Asia would need to invest USD 27 billion in renewable energy every year to achieve the target of 23% renewables in the primary energy supply by 2025 (Vakulchuk et al., 2023). The region has the youngest coal power fleet in the world, with an average plant age of about 12 years in 2022 (Demoral et al., 2022).…”
Section: Demanding—no Easy Path For Energy Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy transition is resource intensive. Southeast Asia would need to invest USD 27 billion in renewable energy every year to achieve the target of 23% renewables in the primary energy supply by 2025 (Vakulchuk et al., 2023). The region has the youngest coal power fleet in the world, with an average plant age of about 12 years in 2022 (Demoral et al., 2022).…”
Section: Demanding—no Easy Path For Energy Transitionmentioning
confidence: 99%
“…Previous studies have typically concentrated on specific aspects of technology, social factors, or the economics of Southeast Asiaʼs energy transition (e.g., Aleluia et al, 2022;Bai et al, 2023;Erdiwansyah et al, 2019;Gu et al, 2023;Vakulchuk et al, 2023). Some studies have discussed unique challenges faced by individual countries (e.g., Do et al, 2022;Guild, 2019;Le et al, 2023;Setyawati, 2020;Urban et al, 2018;Vaka et al, 2020).…”
mentioning
confidence: 99%
“…These policies range from tax credits and subsidies to feed-in tariffs and green bonds. Financial institutions are taking advantage of these incentives by directing their capital towards renewables (Vakulchuk et al, 2023). In addition to direct investments, financial institutions are also developing innovative financing mechanisms for renewables.…”
Section: Introductionmentioning
confidence: 99%
“…Investment in renewable energy will pay off handsomely for Organization for Economic Cooperation and Development nations that use renewable energy at a specific level (Wang and Wang, 2020). Vakulchuk et al (2023) developed a review model to examine the reasons for not attracting more capital to ASEAN countries. Authors primarily focused on legislation, governance reform and investment climate and found that regulatory practices are not up to date, there is ubiquitous carbon lock-in, and no major pro-renewable energy governance reform in ASEAN countries has been implemented except for Malaysia and Vietnam.…”
Section: Introductionmentioning
confidence: 99%